Int J Analyt Bioanalyt Methods 2021
DOI: 10.35840/2633-8912/2416
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Favipiravir in Human Plasma by Using Liquid Chromatography-Tandem Mass Spectrometry: Application to Pharmacokinetic Studies

Abstract: The outbreak of Covid-19 infection has become a pandemic affecting millions of people throughout the world. No specific antiviral drugs have been approved for the treatment of Covid-19. The antiretroviral drug favipiravir (FAV) has been experimentally used for COVID-19 treatment since March 2020 in Japan. China's Science and Technology Ministry official announced that Japan-based anti-flu drug FAV has been observed to help Covid-19 patients recover. Because of that, a simple LC-MS/MS method for the quantificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Stability studies were performed as bench top study and freeze-thaw stability studies and the coefficient of variation was found to be within 3%. The validated method was found to be precise and sensitive and can be applied to pharmacokinetic studies of Favipiravir-marketed formulations 35 . Paul Curley et al developed a highly sensitive bioanalytical assay to quantify Favipiravir using liquid chromatography-tandem mass spectrometry.…”
Section: Shyamala Et Al Developed Forced Degradation Studies For the ...mentioning
confidence: 99%
“…Stability studies were performed as bench top study and freeze-thaw stability studies and the coefficient of variation was found to be within 3%. The validated method was found to be precise and sensitive and can be applied to pharmacokinetic studies of Favipiravir-marketed formulations 35 . Paul Curley et al developed a highly sensitive bioanalytical assay to quantify Favipiravir using liquid chromatography-tandem mass spectrometry.…”
Section: Shyamala Et Al Developed Forced Degradation Studies For the ...mentioning
confidence: 99%